The validity of the diagnosis of depression in general practice: is using criteria for diagnosis as a routine the answer? - van Weel-Baumgarten, E M (2000)
BACKGROUND: In general practice, making a diagnosis does not follow the same lines as in secondary care because every new diagnosis is made against 'foreknowledge' and could be coloured by it. This could explain low accordance and differences in diagnoses between primary and secondary care, in particular when mental illness such as depression is concerned. When criteria are used for diagnosis there should be no differences. AIM: To establish the accordance with the Diagnostic and Statistical Manual of mental disorders, 4th edition (DSM-IV) criteria of major depressive disorder when the diagnosis of depression has been made by general practitioners (GPs) for whom coding and using criteria for diagnosis is a daily routine (ICHPPC-2 criteria). METHOD: Ninety-nine general practice patients from four general practices belonging to the Continuous Morbidity Registry (CMR) of the University of Nijmegen in The Netherlands were interviewed using the Composite International Diagnostic Interview (auto) 12-month version (DSM-IV criteria). Thirty-three patients had a code for depression; 33 patients a code for chronic nervous functional complaints (CNFC); and 33 had no code for mental illness (the depression and CNFC codes were given in the 12 months prior to the interview). Specificity and accordance with the DSM-IV criteria of major depressive disorder (MDD) were calculated with the results from the interviews. RESULTS: Of the 33 general practice depression cases (all matching ICHPPC-2 criteria), 28 matched DSM-IV criteria: 26 for MDD and 2 for dysthymia. No cases of DSM-IV MDD were found in the control group without a code for a mental disorder, and seven out of 33 were found in the control group with the code for CNFC. CONCLUSION: The specificity of diagnosis of depression made by GPs in a continuous morbidity registry and the accordance with DSM-IV criteria are high. Using criteria for diagnosis, which is a trend, could be one of the solutions towards a better diagnosis. As far as the sensitivity is concerned, GPs should not be distracted from using criteria for the diagnosis of depression when a large variety of complaints is presented.